Optimal conditions for cold-shock induction of triploidy in red tilapia - Padmaja, J.P.; Srijaya, T.C.; Anuar, H.; Anil, K.C.; Boonsirm, W.; Andrew, J. (Kluwer (now part of Springer), 2014)
Production of sterile triploid red tilapia [Oreochromis mossambicus (Mozambique tilapia); Peters, 1852 x Oreochromis niloticus (Nile tilapia); Linnaeus, 1758] is an effective strategy to overcome their prolific breeding. Optimal conditions for cold-shock induction of triploidy in red tilapia were investigated by experimentally examining two variables: appropriate temperature of the shock and duration of shock treatment. A constant time after insemination of 4 min was used to determine the best combination of temperature (6, 7, 8, 9, 11, 13, 15 A degrees C) with different durations of shock (10, 20, 30, 40, 50 min) with resultant ploidy level verified karyotypically. Shock duration for 30 min at a temperature of 9 A degrees C was found most effective in producing maximum triploidy (98.7 %) with higher rates of hatching (63.2 %) and survival up to yolk-sac stage (75.8 %). The chromosome count confirmed that triploid percentages were higher when cold shock was used for longer durations at each temperature; however, hatching rates were generally decreased. The maximum triploid yield (82.1 %) obtained was higher than the yield obtained using heat shock (72.7 %) in red tilapia previously. The application of the results of this study has the potential to greatly improve the production of triploid red tilapia in commercial aquaculture.